Efeito da eletroacupuntura na periodontite experimental em ratos com artrite reumatoide - Gusmão, Jonas Nogueira Ferreira Maciel (2019)
Rheumatoid arthritis (RA) and periodontitis are chronic and progressive inflammatory diseases. Studies show the association between these two conditions by environmental, genetic and immunological way. Electroacupuncture (EA) has shown anti-inflammatory effects on experimental periodontitis (EP) and RA. The purpose of this study was to evaluate the effects of EA on the development and progression of experimental periodontitis (EP) in rats with RA. Wistar rats were divided into seven experimental groups (n = 6): (1) Group C (control); (2) Group RA (animals with RA); (3) Group RA/EA (animals with RA and treated with EA); (4) Group EP (EP); (5) EP/EA Group (EP and EA-treated); (6) EP/RA Group (arthritic animals with EP); and (7) RA/EP/EA Group (EP and EA-treated arthritic animals). On day 0 in the RA groups, RA induced subcutaneous injection of bovine collagen type II (CII) emulsified in incomplete Freund's adjuvant (IFA) into the base of the tail. On day 07, a booster dose of CII with IFA was administered. On day 28, in the EP groups, periodontitis was induced by a ligature around the left upper second molar, which remained in position for 11 days. EA was started one day before the booster injection with CII + IFA and every three days until the end of the experimental protocol (36th day). All animals were euthanized 39 days after the onset of experimental RA. The maxillae were removed, and several parameters were evaluated: (1) macroscopic analysis of alveolar bone loss; (2) histomorphometric analysis for quantification of furcation bone loss; and (3) immunohistochemistry for interleukins (IL)-6 and -17 and nuclear factor (NF)-κB in periodontal tissues. Gingival tissue around the second upper molar was collected for the quantification of IL-1β. Paw edema and nociceptive threshold were measured by plestimometer and digital analgesimeter, respectively. Histomorphometric and macroscopic analyses showed that there were no significant differences between the Control and EP/EA groups. Treatment with EA did not reduce alveolar bone loss in the RA/EP group. The groups treated with EA showed reduced IL-6 and -17 immunolabeling, while NF-κB was observed only in the animals of the RA/EP group. EA treatment caused a significant reduction in IL-1β levels in gingival tissue only in the presence of EP. Within the limits of the present study, it can be concluded that EA reduces the inflammatory parameters, but not alveolar bone loss, in EP in arthritic rats.